A meta-analysis reveals earthworms as mutualists rather than predators of soil microorganisms - Manuel Blouin; Aïssa Robin; Lysandre Amans; Frédérique Reverchon; Isabelle Barois; Patrick Lavelle (Geoderma)
Microorganisms constitute the largest biomass on Earth after plants, and earthworms are one of the main components of animal biomass. Both are critical drivers of soil functions and ecosystem services. Studies report either positive or negative effects of earthworms on soil microbial communities, leading to contrasting views on whether microorganisms serve as prey or mutualists for earthworms. This meta-analysis aimed to settle this debate, and examines how biotic and abiotic factors affect earthworm impacts on microbial abundance and diversity. Based on a selective search retaining only genuinely quantitative approaches, we kept 169 observations, showing that, on average, earthworms increased bacterial abundance by 16.5 % and fungal abundance by 31.4 %. Bacterial species richness rose by 8.5 % in the presence of earthworms, but fungal richness was not significantly affected. Epigeic and anecic earthworms had more notable effects than endogeics. Plant presence in experimental designs strongly amplified earthworms’ effects on bacterial (+30 %) and fungal (+97 %) abundances. The largest earthworm-induced effects were observed in carbon- and nitrogen-rich soils and at low pH, while the addition of organic matter reduced these effects. Comparing microbial abundance in earthworm casts to control units without earthworms revealed effect sizes two- to three-fold greater (for bacteria and fungi, respectively) than when using the soil surrounding earthworm casts as a control. Our meta-analysis demonstrates that, despite ingesting some microorganisms, earthworms have a net positive effect on their abundance, positioning them as mutualists rather than predators of bacteria and fungi.